Evaluation of in Vitro Anti-inflammatory and Antioxidant Activity of Selected Zimbabwean Plant Extracts. Issue 2 (2nd April 2016) - Chirisa, Elaine; Mukanganyama, Stanley
ABSTRACT: The in vitro anti-inflammatory and antioxidant activities of Zimbabwean medicinal plant extracts were investigated by COX-1 and COX-2 enzyme inhibitory activity, the erythrocyte membrane stabilization, and albumin denaturation inhibition assays; free-radical scavenging activity of the plant extracts was determined using the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and tetramethoxy azobismethylene quinone (TMAMQ) radical scavenging assays. Combretum zeyheri, C. molle, and Parinari curatellifolia inhibited COX-2, inhibiting COX-1 the least with inhibitions of 42, 68, and 77%, respectively, for COX-2. C. platypetalum selectively inhibited COX-2 by 85% and COX-1 inhibition by 42%. IC50 of C. platypetalum and indomethacin for COX-2 were 571 and 414 µg.mL –1, respectively. C. platypetalum, C. molle, and Brachystegia boehmii stabilized the erythrocyte membrane and inhibited the precipitation of proteins in vitro . Plant extracts that inhibited the COX enzymes were tested for antioxidant activity using the DPPH and the TMAMQ free-radical scavenging assays. P. curatellifolia extract showed potent antioxidant activity in both assays with 100% of the radicals quenched at 16 and 18 µg.mL –1, respectively.